Transforming Settlements of the Urban Poor in Uganda : A Secondary Cities Support Programme - Cities Alliance (World Bank, Washington, DC, 2013)
This report describes theTransforming Settlements of the Urban Poor in Uganda. A Secondary Cities Support Program (TSUPU), is the first national initiative within the Cities Alliance's global programme, Land, Services and Citizenship for the Urban Poor (LSC). The first premise of the Medium Term Strategy is that the Cities Alliance should prioritise working with those governments already committed to change and reform over time for three main reasons: the Cities Alliance support will have a far greater impact, and the opportunities for learning and knowledge sharing will be greatly enhanced, and the model or example to other cities or countries will be more emphatic. Based on this, a program has been designed to support a selected group of developing countries who have recognized the importance of dealing with the challenge of rapid urbanisation, growing cities and deepening urban poverty. The report outlines the activities the TSUPU has designed, that will help the Ugandan government to identify and capture the positive elements of urbanisation, and create inclusive cities without slums in order to maximise the potential of urbanisation by proactively managing urban growth.